Analisis Kebijakan Perpajakan Terhadap Keberlangsungan Perjuangan Mikro Kecil Serta Menengah (UMKM) (Studi Masalah Pada Pasar Sentral Makassar) - Podalla, Jein; Hendrawan (STIEM BONGAYA, 2025)
Analysis of Tax Policy on the Sustainability of Micro Smalland Medium Enterprises (MSMEs) (Case Study at Makassar Central Market).Tax policy is a crucial instrument in supporting economic growth. This study aims to analyze Tax Policy on the Sustainability of Micro, Small, and Medium Enterprises (MSMEs), using quantitative methods and primary data sources in the form of questionnaires, observations, and documentation, using final income tax calculations. There is a significant impact of Tax Policy on the Sustainability of MSMEs at Makassar Central Market and the need for further efforts to design more responsive and inclusive tax policies for the MSME sector. By considering various aspects and factors that influence the impact of tax policies, it is safe for the growth and development of MSMEs.